Respuesta :

Answer:

The present age of Sam is 20 years .

Step-by-step explanation:

Given as :

Let The age of John =  J years

Let The age of Sam = S years

∵ Sam is 12 years older than John

so,  The age of Sam = 12 + The age of John

i.e S = 12 + J            .....1

Again

Before 5 years ago

The age of Sam = 5 times age of John

So, (S - 5) = 5 × (J - 5)

Or, S - 5 = 5 J - 25

Or, 5 J - S = 25 - 5

Or, 5 J - S = 20                  .........2

Solving eq 1 and eq 2

[5 J - (12 + J)] = 20

Or, 5 J - 12 - J = 20

Or, 4 J = 20 + 12

Or, 4 J = 32

∴ J = [tex]\frac{32}{4}[/tex]

i.e J = 8 years

So, The age of John = J = 8 years

Put The value of J into eq 1

∵ S = 12 + J

So, S = 12 + 8

i.e S = 20 years

So, The present age of Sam = S = 20 years .

Hence, The present age of Sam is 20 years . Answer

Answer:

Sam is 20 years old now.

Step-by-step explanation:

Given:

Sam is 12 years older than John.

For the last four years, Sam and John have been friends.

Five years ago, Sam was 5 times as old as John.

Now, to find the age of Sam now.

Let the age of Sam be [tex]x.[/tex]

And the age of John be [tex]y.[/tex]

As, Sam is 12 years older than John.

Thus, [tex]x=12+y[/tex] .....( 1 )

Now, to get the age:

According to question:

[tex]x-5=5(y-5)[/tex]

[tex]x-5=5y-25[/tex]

[tex]x=5y-20[/tex] .....( 2 )

Now, substituting the value of equation (1) in equation (2) we get:

[tex]12+y=5y-20[/tex]

Getting the variables in one side and numbers on the other we get:

[tex]12+20=5y-y[/tex]

[tex]32=4y[/tex]

Dividing both sides by 4 we get:

[tex]8=y[/tex]

[tex]y=8.[/tex]

The age of John = 8 years.

Now, putting the value of [tex]y[/tex] in equation (1) we get:

[tex]x=12+y[/tex]

[tex]x=12+8\\x=20.[/tex]

Age of Sam = 20 years.

Therefore, Sam is 20 years old now.